(untitled) (International journal of artificial intelligence, 2025)
This article discusses the formation of musical literacy on the basis of the age-old traditions of teacher-student, as well as the development of new technologies in this process, as well as the implementation of educational processes based on existing pedagogical technologies. Our esteemed President Sh. Mirziyoyev has always recognized that art and culture are an important factor that introduces each nation to the world. In this regard, our government is carrying out a lot of effective work to educate the younger generation in a comprehensive and advanced way. The article also emphasizes the concept of musical pedagogy, that is, the creative activity of a music teacher and pedagogical approaches in the processes of working with students.